Políticas de ventas para la sostenibilidad de la cooperativa de producción, industrialización, comercialización Santa Fé Coopincosan - Calero Cherres, . Mariana Isabel (2019)
The Sales Policies for the Sustainability of the Cooperative de Production, Industrialization, Commercialization Santa Fé COOPINCOSAN belonging to the province of Bolívar, canton Guaranda, Santa Fé parish arise from the ignorance of the behavior of the products in the market, whose specific objectives. Cooperatives were to diagnose the current situation of the company, identify the processes, management that meets the sales department, formulation of sales policies for the marketing of products and socialization that will respond to the sustainability of the cooperative. The methodology to be applied were the exploratory, descriptive and deductive methods, surveys applied to the universe of the partners, with the use of a questionnaire that was statistically validated by the chronbach's Alpha internal consistency method. The main results of the research were the lack of commercialization on the part of the members of the cooperative, the lack of promotion causing sales decrease, causing the benefits perceived by the cooperative to decrease, price instability, and lack of access to markets It is proposed the implementation of three sales policies with two strategies, a marketing channel and a promotion plan, aspects that will guarantee the trend in the behavior of the products offered by the cooperative throughout its life. It is concluded that the formation of organizations is important for the emergence of the Bolivar province, however, this cooperative, since it does not have knowledge regarding the behavior of the products in the market, may disappear, for this reason the sales policies will help to re-vitalize its products as its recognition through the brand, creating